Successful Advanced Maternal Age Pregnancy with Mosaic Turner Syndrome Conceived after Ovulation Induction with Clomiphene Citrate: A Case Report - Masahiro Murakami; Kenji Hinokio; Machiko Kiyokawa; Mikio Morine; Takeshi Iwasa (Hindawi Limited, 2014)
Turner women typically experience gonadal dysfunction that results in amenorrhea and sterility. We encountered a case of mosaic Turner syndrome where conception was possible after ovulation induction with clomiphene citrate (CC). The patient's ovaries were overresponsive to induction with CC. The challenges and successful outcome are reported.